Quantifying the effect of commercial nitrogen formulations BlackUrea™ / BlackDAP™ as alternative nitrogen source on fruit tree physiology, yield and fruit quality of two apple cultivars - Janse van Vuuren, Liaan (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScAgric)--Stellenbosch University, 2018.